MEWUJUDKAN KEBERHASILAN KERJA MELALUI PERSEPSI LOCUS OF CONTROL INDIVIDU KARYAWAN SEMEN BUMN - Andi Ririn Oktaviani (BJRM (Bongaya Journal of Research in Management), 2018)
This study aims to identify perceptions of attitudes of cement employees ofBUMN in carrying out work to achieve job success. The method for collecting data inthis study uses questionnaires and interviews and analysis techniques with structuralequation models (SEM). The results of this study indicate that the tendency of internallocus of control owned by most cement employees of BUMN plays an important role asan employee work stimulus to succeed in his job